A unique presentation of Graves' disease in a pregnant woman with severe hypothyroidism. (3rd August 2022) - Rotondi, Mario; Bendotti, Giulia; Croce, Laura; Molteni, Martina; Carbone, Andrea; Magri, Flavia; Pearce, Elizabeth N.; Chiovato, Luca
Abstract: Background Graves' disease occurrence during pregnancy is not a frequent event, showing an incidence of 0.2-0.4% in unselected pregnant women. Depending on their functional properties, TSH-receptor antibodies can induce hypothyroidism or hyperthyroidism. Recognizing the signs of altered thyroid function is essential to prevent possible complications on the fetus. Materials and methods The case of a pregnant woman without previous history of thyroid disease presenting with severe overt hypothyroidism during the first trimester is reported. Levothyroxine therapy was started and 6 weeks later overt hyperthyroidism was observed. TRAb were detected at high titers. Levothyroxine was withdrawn and low dose methimazole was started. Serial obstetric ultrasound scans were negative for indirect signs of fetal thyroid dysfunctions and no fetal goiter was visualized throughout pregnancy. Spontaneous delivery occurred without complications at 39 weeks of gestation. In the post-partum, severe overt hypothyroidism recurred, thus methimazole was discontinued and levothyroxine was restarted. TRAb persisted at high levels. The infant experienced a transient thyrotoxicosis, which fully resolved in three months with normalization of thyroid function and negativization of TRAb levels. Results The present case report allows us to overview the challenges related to the management of hypo and hyperthyroidism in patients with high TRAb levels, requiring strict monitoring aimed at early detection of both maternal and fetal consequences. Conclusions This case underlines the importance of close follow-up and the need of collaboration in a multidisciplinary team when Graves's disease is diagnosed in a pregnant woman to prevent adverse neonatal outcomes.